The Effect of Leadership Style, Self-Efficiency, Work Environment and Work Motivation on Job Satisfaction During Covid19 Pandemic (Case Study of Lecturer of Manado State University) - Karisoh, Gabriel Dave Janma; Lumanauw, Bode; Trang, Iran (European Journal of Life Safety and Stability (2660-9630), 2021)
In the midst of the COVID19 pandemic era, it shows that many factors have changed for us to work in 2020. Some of the factors that influence us are leadership style, self-efficacy, work environment and work motivation. influence of leadership style, self-efficacy, work environment and work motivation on job satisfaction of Manado State University Lecturers. This research uses the independent variables of leadership style, self-efficacy, work environment and motivation and the dependent variable is job satisfaction. This research is quantitative methodology using multiple linear regression as data analysis technique where data is obtained by sharing questionnaires to 90 respondents. The population & sample is using Likert scale of all of Manado State University Lectures.